2017
DOI: 10.1093/gerona/glw234
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Frailty in Older Patients With Early-Stage Solid Tumors: A Prospective Longitudinal Evaluation of Three Different Geriatric Tools

Abstract: A VES-13 score of ≥7 is a valuable discriminating tool for predicting functional decline or death and can be used as a frailty-screening tool among older cancer patients in centers with limited resources to conduct a comprehensive geriatric assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Our results are consistent with other studies in the literature. Specifically the prevalence of frailty, assessed by the FFI, in our cohort of advanced lung cancer patients was similar to that reported in studies of older adults cancer patients (12–35%) [3032]. The prevalence of deficits detected by the cancer specific GA was also consistent with reports among older adults with varied cancer types with a substantial proportion demonstrating impairments in physical function, emotional health and high levels of comorbidity [9, 11, 12, 33, 34].…”
Section: Discussionsupporting
confidence: 85%
“…Our results are consistent with other studies in the literature. Specifically the prevalence of frailty, assessed by the FFI, in our cohort of advanced lung cancer patients was similar to that reported in studies of older adults cancer patients (12–35%) [3032]. The prevalence of deficits detected by the cancer specific GA was also consistent with reports among older adults with varied cancer types with a substantial proportion demonstrating impairments in physical function, emotional health and high levels of comorbidity [9, 11, 12, 33, 34].…”
Section: Discussionsupporting
confidence: 85%
“…One study found that G8 scores were predictive of early functional decline in 292 patients treated with first-line chemotherapy [282]. A second study found the Fried physical frailty phenotype and the VES-13 scores, but not frailty according to the Balducci criteria, to be predictive of functional decline in 185 older cancer patients with solid tumors mainly receiving systemic treatment [283]. A third study, however, reported neither the GFI, G8, VES-13, nor the aCGA to be predictive of functional decline in 134 cancer patients, amongst whom 29% received chemotherapy [284].…”
Section: Frailty In Older Cancer Patientsmentioning
confidence: 99%
“…2) Thus, it is important to quantify this variability or frailty to identify individuals at a significant risk of developing disability despite initial independence. 3) The vulnerability of a frail person is obvious when comparing their functional capacity to that of a non-frail person after physiological stress. For example, after minor surgery, an older person is expected to recover to their baseline function.…”
Section: Introductionmentioning
confidence: 99%
“… 2 ) Thus, it is important to quantify this variability or frailty to identify individuals at a significant risk of developing disability despite initial independence. 3 )…”
Section: Introductionmentioning
confidence: 99%